Preparation method of phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material
By using phosphate and polyethylene oxide modified silicon/graphite double-layer anode material in lithium-ion batteries, the problem of insufficient ionic conductivity and stability of traditional materials is solved, and higher conductivity and cyclic stability are achieved.
Patent Information
- Application Number
- CN202411855797.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
AI Technical Summary
The ionic conductivity and specific capacity of traditional graphite negative electrode materials cannot meet the high requirements of new energy vehicles for the energy density, cycle life and safety performance of lithium-ion batteries. In addition, silicon-based lithium batteries have volume expansion and electrolyte side reactions during charging, resulting in poor structural and interface stability.
Using phosphate and polyethylene oxide modified silicon/graphite bilayer anode material, silicon particles are modified by lithium phosphate and glucose-covered carbon treatment, combining polyethylene oxide and graphite layer to form a stable lithium ion transport interface.
It improves the transmission efficiency of lithium ions, enhances the conductivity and cycling stability, alleviates the volume expansion effect of silicon materials, and improves the electrochemical performance of lithium batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure HDA0005191773600000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of negative electrode materials for lithium ion batteries, and in particular to a method for preparing a silicon / graphite double-layer negative electrode material modified by phosphate and polyethylene oxide. Background Art
[0002] With the continuous development of new energy vehicles, higher requirements are placed on the energy density, cycle life and safety performance of lithium-ion batteries. The field of power battery materials continues to develop in the direction of high specific capacity, high charge and discharge efficiency and long cycle life. The ion conductivity and specific capacity of traditional graphite negative electrodes are low and can no longer meet the needs of new energy vehicles. Silicon anode has become one of the most promising negative electrode materials due to its high energy density, high charge and discharge efficiency and rich content.
[0003] There are also certain problems with silicon negative electrode materials. During the charging process of lithium-ion batteries with silicon negative electrodes, the silicon negative electrode will expand in volume, and the electrolyte will undergo side reactions, resulting in poor structural and interfacial stability, which will cause the capacity to be greatly reduced with the cycle, hindering its practical application. The safety hazards caused by the uncontrollable dendrite growth of the negative electrode and the unstable solid electrolyte interface film (SEI film) during the cycle of silicon-based lithium batteries and the low coulomb efficiency of the battery have seriously hindered the development of lithium batteries. Secondly, lithium batteries also have problems such as low lithium ion conductivity. Therefore, it is necessary to improve the volume expansion and low conductivity of silicon-based negative electrode materials, while ensuring the high capacity of silicon-based lithium batteries, improve the stability of the battery, improve the main problems of silicon-based lithium batteries, and promote the development of the lithium battery field, so as to adapt to the development of new energy vehicles. Summary of the invention
[0004] In order to solve the above-mentioned technical problems in the development of lithium batteries, the present invention provides a phosphate and polyethylene oxide modified silicon / graphite double-layer negative electrode material and a preparation method thereof. Silicon particles are modified by lithium phosphate, and the modified silicon particles are treated with glucose carbon coating at the same time. The modified silicon particles are mixed with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose, and styrene-butadiene rubber and dissolved in water, and the mixed solution is applied to copper foil to obtain a silicon-based battery pole piece; graphite and polyethylene oxide are dissolved in water, and the mixed solution is applied to a silicon-based battery pole piece to obtain a silicon / graphite double-layer negative electrode. The obtained negative electrode has good electrochemical properties and high ionic conductivity.
[0005] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:
[0006] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and perform ball milling to obtain silicon powder modified with lithium phosphate, i.e., a precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tube furnace under air atmosphere to obtain a modified material Si@LPO;
[0007] (2): The material Si@LPO is stirred and uniformly dispersed in an ethanol solution containing glucose to obtain a mixed solution, the mixed solution is placed in an oil bath for heating and continuously stirred to dry, the dried material is placed in an oven for drying again to obtain the material Si@LPO@glucose, and the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere to obtain the material Si@LPO@C;
[0008] (3): The material Si@LPO@C is mixed with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolved in water, the mixed solution is applied on copper foil, and the coated copper foil is placed in a vacuum oven for drying to obtain a silicon-based battery electrode;
[0009] (4): Mix the graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water. Apply the mixture on the silicon-based battery electrode. Put the coated copper foil into a vacuum oven and dry it to obtain a silicon / graphite double-layer negative electrode.
[0010] Preferably, in step (1), the ball milling speed is 200-400 r / min, the ball milling time is 1-2 h, the sintering temperature is 350-400° C., and the sintering time is 0.5-1 h.
[0011] Preferably, in step (2), the stirring speed is 500 r / min, the stirring time is 8-12 h, the oil bath temperature is 90-100 ° C, the oil bath is kept until the ethanol is completely evaporated, the oven drying temperature is 80-90 ° C, the drying time is 8-12 h, and the pyrolysis treatment is heated to 750-800 ° C at a heating rate of 5-10 ° C / min and kept warm for 3-4 h.
[0012] Preferably, in step (3), the mass ratio of Si@LPO@C to the total weight of the five raw materials is 65% to 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 0 to 15%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0013] Preferably, in step (4), the mass ratio of graphite to the total weight of the five raw materials is 65% to 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5 to 15%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0014] Preferably, in steps (3) and (4), the vacuum oven drying temperature is 60 to 80° C., and the drying time is 8 to 12 hours.
[0015] The beneficial effects of the present invention are
[0016] 1. The silicon material forms a lithium phosphate layer through sintering on the surface, which can reduce the energy barrier for lithium ions to be transported from the lithium phosphate shell to the Si negative electrode, improve the transmission efficiency of lithium ions, and thus improve the conductivity of lithium-ion batteries.
[0017] 2. Polyethylene oxide has good lithium performance and mechanical properties. The negative electrode material obtained by mixing the modified silicon material with polyethylene oxide to make a slurry can alleviate the volume expansion effect of the silicon material and have a more stable lithium ion transmission channel, thereby improving the stability of the silicon-based negative electrode.
[0018] 3. The surface of the modified silicon material is treated with carbon. Due to the good stability of carbon, the stability of the negative electrode of the lithium battery is further improved. At the same time, the double-layer negative electrode structure with a graphite layer added to the surface of the silicon layer further suppresses the expansion effect of the silicon-based negative electrode. Combined with the joint action of the above materials, a more stable lithium ion transmission interface is formed, which improves the lithium ion conductivity of the silicon-based negative electrode material and comprehensively improves the electrochemical performance of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the negative electrode structure in an embodiment of the present invention;
[0020] Among them, 1-current collector; 2-first negative electrode active material layer (modified silicon layer); 3-second negative electrode active material layer (graphite). DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that these descriptions are exemplary only and are not intended to limit the scope of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0022] Example 1
[0023] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 400 r / min for 1 hour to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 0.5 h to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 5%.
[0024] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0025] (3): Mix the material Si@LPO@C with acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 80%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0026] Example 2
[0027] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 200 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 0.5 hours to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 10%.
[0028] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 5°C / min, and the temperature is maintained for 4 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 10%.
[0029] (3): Mix the material Si@LPO@C with acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 80%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0030] Example 3
[0031] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 400 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 350°C for 1 hour to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 5%.
[0032] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 4 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0033] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0034] Example 4
[0035] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 350 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 0.5 hours to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 10%.
[0036] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 4 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 15%.
[0037] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0038] Example 5
[0039] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 400 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 0.5 hours to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 5%.
[0040] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0041] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0042] Example 6
[0043] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 350 r / min for 1 hour to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 350°C for 1 hour to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 10%.
[0044] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 5°C / min, and the temperature is kept for 3 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 15%.
[0045] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0046] Example 7
[0047] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 400 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 1 hour to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 5%.
[0048] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0049] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0050] (4): Mix graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene butadiene rubber and dissolve them in water, apply the mixture on the silicon-based battery pole piece, put the coated copper foil into a vacuum oven for drying, and obtain a silicon / graphite double-layer negative electrode. The mass ratio of graphite to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene butadiene rubber to the total weight of the five raw materials is 7%.
[0051] Example 8
[0052] (1): Put silicon powder, lithium hydroxide and diammonium phosphate into a ball mill, and ball mill them at 400 r / min for 1 hour to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 350°C for 0.5 h to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 10%.
[0053] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 5°C / min, and the temperature is maintained for 4 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0054] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0055] (4): Mix graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene butadiene rubber and dissolve them in water, apply the mixture on the silicon-based battery pole piece, put the coated copper foil into a vacuum oven for drying, and obtain a silicon / graphite double-layer negative electrode. The mass ratio of graphite to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene butadiene rubber to the total weight of the five raw materials is 7%.
[0056] Example 9
[0057] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 400 r / min for 2 hours to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 0.5 hours to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 5%.
[0058] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 800°C at a heating rate of 10°C / min, and the temperature is kept for 3 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 20%.
[0059] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0060] (4): Mix graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene butadiene rubber and dissolve them in water, apply the mixture on the silicon-based battery pole piece, put the coated copper foil into a vacuum oven for drying, and obtain a silicon / graphite double-layer negative electrode. The mass ratio of graphite to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene butadiene rubber to the total weight of the five raw materials is 7%.
[0061] Example 10
[0062] (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and ball mill them at 350 r / min for 1 hour to obtain lithium phosphate-modified silicon powder, i.e., the precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tubular furnace under an air atmosphere at a sintering temperature of 400°C for 1 hour to obtain a modified material Si@LPO; wherein the mass fraction of LPO is 10%.
[0063] (2): The material Si@LPO is stirred and evenly dispersed in an ethanol solution containing glucose for 12 hours to obtain a mixed solution, the mixed solution is placed in a 90°C oil bath for heating and continuously stirred to dry, the dried material is placed in an 80°C oven and dried again for 12 hours to obtain the material Si@LPO@glucose, the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere, the temperature is increased to 750°C at a heating rate of 5°C / min, and the temperature is kept for 4 hours to obtain the material Si@LPO@C; wherein the mass fraction of C is 10%.
[0064] (3): Mix the material Si@LPO@C with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water, apply the mixture on copper foil, and place the coated copper foil in a vacuum oven at 80°C and dry it for 12 hours to obtain a silicon-based battery electrode; wherein the mass ratio of Si@LPO@C to the total weight of the five raw materials is 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
[0065] (4): Mix graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene butadiene rubber and dissolve them in water, apply the mixture on the silicon-based battery pole piece, put the coated copper foil into a vacuum oven for drying, and obtain a silicon / graphite double-layer negative electrode. The mass ratio of graphite to the total weight of the five raw materials is 70%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 10%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene butadiene rubber to the total weight of the five raw materials is 7%.
[0066] The lithium ion conductivity and cycle performance of the silicon-based negative electrode materials prepared in Examples 1-10 are shown in Table 1, and the comparative sample is a pure silicon sample.
[0067]
[0068]
[0069] Table 1
[0070] Note:
[0071] 1.D is the lithium ion diffusion coefficient, unit is 10 -14 cm 2 / s. 2. The cycle rate is 1A / g.
[0072] The silicon / graphite negative electrode material prepared in Example 7 has a large lithium ion diffusion coefficient before and after cycling, and the capacity is still 444.2 mAh / g after fifty cycles, and has good lithium ion conductivity and cycle stability. Compared with other examples, the silicon / graphite negative electrode material prepared by the formula of Example 7 has the best comprehensive performance in lithium ion batteries.
[0073] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material, characterized in that: Silicon particles are modified by lithium phosphate and treated with glucose-coated carbon. The modified silicon particles are dissolved in water with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber in a certain proportion, and the mixture is applied on copper foil to obtain silicon-based battery electrodes. Graphite and polyethylene oxide are dissolved in water, and the mixture is applied to silicon-based battery electrodes to obtain a silicon / graphite double-layer negative electrode.
2. The method for preparing the phosphate and polyethylene oxide modified silicon / graphite double-layer negative electrode material according to claim 1, characterized in that: The method specifically comprises the following steps: (1): Put silicon powder, lithium hydroxide and ammonium dihydrogen phosphate into a ball mill, and perform ball milling to obtain silicon powder modified with lithium phosphate, i.e., a precursor of the material Si@LPO. Sinter the Si@LPO precursor in a tube furnace under air atmosphere to obtain a modified material Si@LPO; (2): The material Si@LPO is stirred and uniformly dispersed in an ethanol solution containing glucose to obtain a mixed solution, the mixed solution is placed in an oil bath for heating and continuously stirred to dry, the dried material is placed in an oven for drying again to obtain the material Si@LPO@glucose, and the material Si@LPO@glucose is pyrolyzed in a tubular furnace in an argon atmosphere to obtain the material Si@LPO@C; (3): The material Si@LPO@C is mixed with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolved in water, the mixed solution is applied on copper foil, and the coated copper foil is placed in a vacuum oven for drying to obtain a silicon-based battery electrode; (4): Mix the graphite material with polyethylene oxide, acetylene black, sodium carboxymethyl cellulose and styrene-butadiene rubber and dissolve them in water. Apply the mixture on the silicon-based battery electrode. Put the coated copper foil into a vacuum oven and dry it to obtain a silicon / graphite double-layer negative electrode. The mass ratio of Si to LPO in the Si@LPO material is 19:1 to 15:5, and the mass ratio of Si@LPO to C in the Si@LPO@C material is 4:1 to 8:
1.
3. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material as claimed in claim 1 or 2, characterized in that: In step (1), the ball milling speed is 200-400 r / min, the ball milling time is 1-2 h, the sintering temperature is 350-400° C., and the sintering time is 0.5-1 h.
4. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material as claimed in claim 1 or 2, characterized in that: In step (2), the oil bath temperature is 90-100° C., and the oil bath is kept until the ethanol is completely evaporated. The oven drying temperature is 80-90° C., and the drying time is 8-12 h. The pyrolysis treatment is carried out by heating the temperature to 750-800° C. at a heating rate of 5-10° C. / min and keeping the temperature for 3-4 h.
5. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material as claimed in claim 1 or 2, characterized in that: In step (3), the mass ratio of Si@LPO@C to the total weight of the five raw materials is 65% to 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 0 to 15%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
6. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material as claimed in claim 1 or 2, characterized in that: In step (4), the mass ratio of graphite to the total weight of the five raw materials is 65% to 75%, the mass ratio of polyethylene oxide to the total weight of the five raw materials is 5 to 15%, the mass ratio of acetylene black to the total weight of the five raw materials is 10%, the mass ratio of sodium carboxymethyl cellulose to the total weight of the five raw materials is 3%, and the mass ratio of styrene-butadiene rubber to the total weight of the five raw materials is 7%.
7. A method for preparing a phosphate and polyethylene oxide modified silicon-based double-layer negative electrode material as claimed in claim 1 or 2, characterized in that: In steps (3) and (4), the vacuum oven drying temperature is 60 to 80° C. and the drying time is 8 to 12 hours.
Citation Information
Cited By
Carbon-coated lithium iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN120637467A